Marriage as Survival Strategy among the Sephardic Jewsof Saloniki, 1900-1943: Continuity and Change - Hadar, Gila (MiKAN, 2007)
Marriage is the most ancient and importantsocial strategy in Judaism. Its objective, apart from procreation and the production of offspring within a family framework, is to preserve the social order and a value system that sanctifies lineage and possession - the choice of bride and groom, the age of marriage, and the preparations for the marriage ceremony. Every word, color, sound, delicacy, custom and song, had symbolic meaning.These processes took place according to Jewish law and custom and the Iberian tradition, but were influenced by the constraints of everyday life within and alongside the surrounding society, Moslem or Greek. For centuries, marriage served as a means of protecting Jewish society from outside influencesthat threatened its existence. In this article, we shall discuss marriage and mass marriage during the Second World War and on the eve ofthe deportation to the extermination camps, practicesthat circumvented the conventions customary in peacetime, with survival as their primary goal.